2013
DOI: 10.1007/s11064-013-1049-5
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Stress Produces Social Behavior Deficits and Alters the Number of Oxytocin and Vasopressin Neurons in Adult Rats

Abstract: The present study investigated the long-lasting effects of prenatal repeated restraint stress on social behavior and anxiety, as well as its repercussions on oxytocin (OT) and vasopressin (VP)-positive neurons of the paraventricular (PVN) and supraoptic (SON) nuclei from stressed pups in adulthood. Female Wistar rats were exposed to restraint stress in the last 7 days of pregnancy. At birth, pups were cross-fostered and assigned to the following groups: prenatally non-stressed offspring raised by prenatally no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 41 publications
7
71
0
Order By: Relevance
“…While several studies indicated that oxytocin receptor expression and OXTR binding is elevated in several brain areas during parturition and breastfeeding and linked to reduced anxiety and depression in the mother (Lonstein et al, 2014), oxytocin signaling in offspring is less well studied. Intriguingly, rodent studies suggest that exposure to prenatal and postnatal maternal stress decreased the number of oxytocin positive cells in adult offspring as compared with offspring from non-stress exposed mothers (de Souza et al, 2013). Furthermore, prairie vole neonates injected with oxytocin display higher parental behavior, facilitated partner bonding and decreased corticosterone after a swim test later in life, as compared to animals injected with an oxytocin antagonist (Carter, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several studies indicated that oxytocin receptor expression and OXTR binding is elevated in several brain areas during parturition and breastfeeding and linked to reduced anxiety and depression in the mother (Lonstein et al, 2014), oxytocin signaling in offspring is less well studied. Intriguingly, rodent studies suggest that exposure to prenatal and postnatal maternal stress decreased the number of oxytocin positive cells in adult offspring as compared with offspring from non-stress exposed mothers (de Souza et al, 2013). Furthermore, prairie vole neonates injected with oxytocin display higher parental behavior, facilitated partner bonding and decreased corticosterone after a swim test later in life, as compared to animals injected with an oxytocin antagonist (Carter, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, prenatally stressed adult male rats raised by their stress-exposed mothers not only showed impairment in social interactions but also a reduced number of oxytocin-positive neurons in the paraventricular nucleus as compared to adult male offspring born and raised by non-stressed mothers (de Souza et al, 2013). Additionally, elevated activity of the oxytocinergic system is also implicated in a dampening of the stress response by interacting with the hypothalamic-pituitary-adrenal (HPA) axis and sympathetic nervous system (Light et al, 2000;Neumann, 2002;Lee et al, 2009;Grewen and Light, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PRS might have caused an oxytocinergic hypotonus (Lee et al, 2007;de Souza et al, 2013), with an ensuing up-regulation of oxytocin receptors in target regions of hypothalamic oxytocinergic neurons, i.e., the hippocampus and amygdala. Carbetocin treatment reduced oxytocin receptor mRNA levels in the amygdala and hippocampus of PRS rats, and in the amygdala of unstressed rats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, male rats born to mothers who experienced four sessions of restraint per day during the latter stages of pregnancy, exhibit reduced social interactions when repeatedly faced with a single conspecific in a familiar arena in adulthood (88). Interestingly this result was found as part of a social memory test, designed to determine if individuals could recognise a novel conspecific after habituation to a previous one.…”
Section: Long-term Effectsmentioning
confidence: 99%
“…Both pre-natal and juvenile stressors have been shown to significantly alter nonapeptide production in later life (88,(101)(102)(103)(104)(105). Maternal separation of mouse pups for three hours a day in the first two weeks of life causes opposite effects on the two main nonapeptides within the hypothalamus in adulthood; AVP was seen to be significantly upregulated, whereas OT was downregulated (106).…”
Section: Long-term Effectsmentioning
confidence: 99%